Design and Development of a Mini Steam Power Plant 12V DC With an Impulse Turbine - Nurhaida; Susanti, Indah; Wardhani, Dyah Utari Yusa (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
A Steam Power Plant is a system that converts thermal energy into electrical energy through the process of water evaporation and the utilization of a steam turbine. In this report, a mini 12V DC steam power plant is designed using an impulse turbine as the main driver of the generator. The system consists of an LPG-fired boiler that produces pressurized steam to rotate the turbine, enabling the generator rotor to generate electricity. Test results show a maximum output voltage of 12.5 V DC at a rotational speed of 991.5 RPM, with steam input power of 244 watts. Although the theoretical relationship between RPM and generated EMF is linear, the measured output voltage exhibits a non-linear trend due to the integrated voltage regulator. In the load test, the system maintained stable operation, although efficiency naturally decreased under full-load conditions due to the higher current draw. Pressure testing indicates a gradual increase up to 2 bar within 21 minutes, demonstrating stable boiler performance. The system successfully powered several 12V loads, including LED lights, a fan, a buzzer, and a USB charger. This mini steam power plant prototype validates the working principles of a small-scale steam power system and serves as an effective educational tool.